An Service Program Evaluation at KPAI Indonesia - Rahmad Parulian; Hamidah; R. Madhakomala (Journal of Business and Behavioural Entrepreneurship, 2022)
The research on evaluating the KPAI's mediation service program aims to evaluate the effectiveness of the implementation of the mediation program, which includes the input, process and outcome stages at KPAI. This research is classified as evaluative research using an evaluation model framework developed by Robert Stake with three evaluation components, namely: Antecedent (input), Transaction (process) and Outcome (result). Data were collected through document studies, interviews, observation and focus group discussions as well as the credibility of the data. Qualitative data analysis through data collection stage, data reduction stage (summarizing, coding, tracing themes, creating cluster ideas, creating partitions, writing memos), data presentation stage, and conclusion drawing stage. The results of the study can be concluded that in general mediation services at KPAI have been running effectively and efficiently. In general, all aspects evaluated meet the standard criteria set. All evaluation criteria meet the adequacy and accuracy of program implementation. All aspects evaluated have an equal equivalence relationship between the expected goals and the actual conditions that occur.